Immutability and impermanence in Qiu Zhijie's work: From Buddhism to New Confucianism to Mainland New Confucianism. (1st September 2019) - Kayser, Christine Vial
Abstract'The need to go back to the past' is central to Qiu Zhijie (b. 1969)'s understanding of human agency, and in consequence is central to his artistic endeavour. By 'the past' Qiu means Chinese (immutable) history and identity, based on a sense of impermanence. Chinese philosophy has informed his work from its beginning in the 1990s, as he imagined calligraphic performances, infused his installations and photographs with explicit references to Buddhist sutras and Koan. Since 2000 he has peppered his discourse and curating practices with implicit references to Confucianism (such as the celebration of the master/student relationship, the search for social harmony). Initial works used a mix of western contemporary and Chinese traditional art forms, and were concerned to the cultivation of the self. The latter have become associated with social aims such as diffusing art to the masses, promoting ancient arts and crafts in curated projects that link the artist's individual development with that of the collective. Qiu designates this holistic aim as 'Total art'. Critics explain Qiu's concept of Total art using the Wagnerian concept of Gesamtkunstwerk or of post-structural criticality of history. Others compare Qiu's endeavour to Republican New Confucianism. Still others consider it as part of Chinese literati tradition, in an ahistorical perspective. We want to emphasize rather its relation to Mainland New Confucianist philosophy that emerged since the millennium, which is characterized by a will to use ontological Chinese values to defend a political vision of Confucianism that is both social and authoritarian, essentially Chinese and opened to the world. This explains how Qiu reconciles his view of 'going to the past', with his participation in the Government's sponsored international programmes. We shall question its consequence on Qiu's position as global 'avant-garde'.